LEARNING MEDIA BASED ON LOCAL WISDOM THROUGH TRADITIONAL GAMES: CHARACTER BUILDING IN KINDERGARTEN - Siregar, Epi Supriyani; Sari, Ika Purnama; Setiawan, Ari; Nasution, Lukman; Susilawati, Evi (JURNAL EDUSCIENCE, 2025)
Purpose- Character education in early childhood is an essential foundation for forming a generation with noble morals and character. One practical approach to instilling character values is through regional songs and traditional games. Regional songs contain rich cultural values and can stimulate children's emotional and social development. Meanwhile, traditional games teach the values of sportsmanship, cooperation, and discipline, which are very important in children's social lives. This study aims to analyze the effectiveness of regional songs and traditional games in developing the character of early childhood.Methodology—This study used a qualitative and quantitative approach. Qualitative data were analyzed using content analysis techniques, and quantitative data were analyzed statistically using SPSS.Finding- The study results showed that using regional songs significantly fostered values of politeness, love of the homeland, and appreciation for cultural diversity. This study concludes that integrating regional songs and traditional games in learning in early childhood education has proven effective in holistically forming children's characters. Regional songs help instill moral and cultural values, while traditional games shape children's social skills and discipline.Contribution- This approach should be developed and applied more widely in the early childhood education curriculum to strengthen cultural identity and moral values in everyday life.